Ankle-Brachial Index as the Best Predictor of First Acute Coronary Syndrome in Patients with Treated Systemic Hypertension. (17th July 2020) - Myslinski, Wojciech; Stanek, Agata; Feldo, Marcin; Mosiewicz, Jerzy
Abstract : Objective . The objective of our study was to evaluate the incidence of target organ damages (TOD) in patients with arterial hypertension and the first ever episode of myocardial infarction (N-STEMI or STEMI) and to determine which of the analyzed kinds of TOD had the highest predictive value for the assessment of the likelihood of acute coronary syndrome (ACS). Material and Methods . The study group consisted of 51 patients with treated systemic hypertension, suffering from the first episode of myocardial infarction (N-STEMI or STEMI), confirmed by coronary angiography and elevation of troponin. The control group consisted of 30 subjects with treated hypertension and no history of myocardial ischaemia. In all subjects' measurements of blood lipids, hsCRP and eGFR were measured. TOD, such as intima-media thickness (IMT), presence of atherosclerotic plaques, ankle-brachial index (ABI), and left ventricular hypertrophy, were assessed. Results . Age, BMI, blood pressure, and time since diagnosis of hypertension did not differ between the study groups. There were no differences regarding blood lipids and eGFR, while hsCRP was significantly increased in the study group. The left ventricular mass index was similar in both groups. Patients with myocardial infarction had significantly increased IMT and decreased ABI. The statistical analysis revealed that only ABI was the most significant predictor of ACS in the study group. Conclusion . Among several TOD, ABI seems to be the most valuable parameter in the prediction of ACS.